ANALYZING THE FACTORS THAT INFLUENCE ACHIEVEMENT OF EXCLUSIVE BREASTFEEDING AMONGST INFANT AGE 7-12 MONTHS IN THE COMMUNITY HEALTH CENTER CIPONDOH KOTA TANGERANG 2019 - Hakim, Amelia Nurul; Mesra, Erna; Suhanda, Parta (Journal of Applied Health Management and Technology, 2020)
ABSTRACT Background: Exclusive breastfeeding is a concrete effort to obtain a good growth and development for a baby, because breast milk contains all the essential nutrients needed for baby's growth and contains antibodies (colostrum) for the baby's immune system. Based on data sourced from the Directorate General, data obtained for coverage of breastfeeding  in 2015 in Indonesia amounted to 55.7%. Data from the health profile of Kota Tangerang in 2015 amounted to 67.36%, still not reaching the target of 80%. Research Purposes: Analyzing factors that related to the success of exclusive breastfeeding in an infants aged 7 - 12 months in Cipondoh Health Center, Tangerang City. Research Methods: This research uses descriptive quantitative method with cross sectional approach.  Hypothesis testing used chi-square, odds ratio (OR) and multivariate logistic regression analysis. Subjects of all breastfeeding mothers with infants aged 7-12 months who met the inclusion and exclusion criteria, the sample size was 90 respondents with an accidental sampling technique. Result:  Analysis of factors that have a statistically significant relationship with the success of exclusive breastfeeding is mother’s knowledge (p =0.016; OR=17,172; 95%CI; 1,704-173,000). Meanwhile, the relationship between factors of initiation of early breastfeeding, age, education, employment, parity, husband's support, health personnel support and the attitude of mothers with the success of exclusive breastfeeding is not statistically significant. Conclusions and Suggestions: Promotive efforts need to be done on mothers before pregnancy and families about the importance of breast milk. The targets of counseling are health workers, health cadres and the community.